Role of the co-stimulatory molecule inducible T-cell co-stimulator ligand (ICOSL) in the progression of experimental metabolic dysfunction-associated steatohepatitis - Provera, Alessia; Ramavath, Naresh Naik; Gadipudi, Laila Lavanya; Gigliotti, Casimiro Luca; Boggio, Elena; Vecchio, Cristina; Stoppa, Ian; Rolla, Roberta; Boldorini, Renzo; Pirisi, Mario; Smirne, Carlo; Albano, Emanuele; et al. (Frontiers in Immunology, 2023)
Background and Aims: Inducible T-cell Co-Stimulator (ICOS) present on T-lymphocytes and its ligand ICOSL expressed by myeloid cells play multiple roles in regulating T-cell functions. However, recent evidence indicates that reverse signalling involving ICOSL is also important in directing the differentiation of monocyte-derived cells. In this study, we investigated the involvement of ICOS/ICOSL dyad in modulating macrophage functions during the evolution of metabolic dysfunction-associated steatohepatitis (MASH).Results: In animal models of MASH, ICOS was selectively up-regulated on CD8 + T-cells in parallel with an expansion of ICOSL-expressing macrophages. An increase in circulating soluble ICOSL was also evident in patients with MASH as compared to healthy individuals. ICOSL knockout (ICOSL -/-) mice receiving choline/methionine deficient (MCD) diet for 6 weeks had milder steatohepatitis than wild type mice. MASH improvement was confirmed in mice fed with cholesterol-enriched Western diet for 24 weeks in which ICOSL deficiency greatly reduced liver fibrosis along with the formation of crown-like macrophage aggregates producing the pro-fibrogenic mediators osteopontin (OPN) and galectin-3 (Gal-3). These effects associated with a selective shewing of F4-80 + /CD11b high monocytederived macrophages (MoMFs) expressing the Triggering Receptor Expressed on Myeloid cells 2 (TREM2) to CD11b low /F4-80 + cells positive for the Kupffer cell marker C-type lectin-like type 2 receptor (CLEC-2), thus indicating an increased MoMF maturation toward monocyte-derived Kupffer cells. Conclusions: These results suggest that CD8 + T-cells interaction with monocyte-derived macrophages through ICOS/ICOSL critically supports a specific subset of TREM2 + -expressing cells contributing to the evolution of steatohepatitis. The data also point ICOS/ICOSL dyad as a possible target for therapeutic interventions in MASH.